Rosai-Dorfman disease mimicking lung cancer: a case report - Zhang, Caijuan; Gao, Ruoling; Chen, Zhenwei; Huang, Zhilan; Yang, Tian; Hu, Ji Bo (Frontiers in Oncology, 2025)
BackgroundRosai-Dorfman disease (RDD) is an uncommon, benign histiocytic condition with an unclear underlying cause. It typically manifests as painless, bilateral, and significantly enlarged cervical lymph nodes. However, extranodal involvement can also occur, affecting the skin, nasal cavity, bones, orbital tissues, and central nervous system (CNS). Moreover, involvement of the respiratory system is observed in approximately 2% of cases.Case descriptionA 75-year-old female was admitted to our hospital with a one-week history of lumbar and back pain. Chest computed tomography (CT) identified a nodule located in the lung upper right lobe, characterized by spiculated margins and proximal bronchial atresia, raising suspicion for lung cancer. The patient subsequently underwent thoracoscopic lobectomy. Postoperative histopathological examination and immunohistochemical analysis confirmed the diagnosis of RDD.ConclusionPulmonary RDD is rare and can be easily mistaken for other tumors or inflammatory diseases because of its nonspecific clinical and radiological features. Definitive diagnosis requires histopathological evaluation and immunohistochemical analysis.